PERANCANGAN INTERIOR PUSAT PELATIHAN DAN PRASARANA EDUKASI VEGETARIAN DI KABUPATEN TABANAN (Jurnal iSpectrum, 2023)
Vegetarian is a word that defines the condition of a person who has a diet not to eat meat, only to eat foods that come from plants. Many people think that vegetarian food is synonymous with boring food, only vegetables and fruit. Vegetarian people are usually for health reasons, but not only that, it can also be due to certain traditions and diets. Nowadays, it is difficult to find a place that specifically facilitates vegetarians, from places to eat, to buy food ingredients, to places for cooking courses for vegetarian preparations. The type of synthesis method used is the analogy synthesis method, where analogy itself is an analytical method that processes designs with the usual form approach or adapted original form. In this method there are several processes such as transformation, making design schematics and getting themes and concepts for design. The purpose of this design is to create facilities that support vegetarian specialties that can provide convenience for lacto-vegetarians and non-vegetarians, by providing a comfortable interior atmosphere, by applying elements that exist in the natural surroundings. The themes and concepts used are the Unity of Nature theme and the Leaf Analogy concept. In the interior applying a cool and comfortable atmosphere in nature, using natural stone and wood materials, and using firm and curved shapes. It aims to create a different and unique and different experience.